The Effect of Shear Connectors on Cold-Formed Steel as Hybrid Beam Reinforcement - Puluhulawa, Indriyani; Alamsyah,; Listianti, Ajeng (International Journal of Integrated Engineering, 2025)
Hybrid beams are critical components in structural engineering, often reinforced with high-tensile-strength materials that surpass conventional reinforcement bars. Cold-Formed Steel (CFS) is a commonly utilized material in this context, offering enhanced structural performance, durability, and load-bearing capacity. However, previous studies indicate that the incorporation of the CFS in hybrid beams often leads to a strength reduction of approximately 50% compared to theoretical expectations. This discrepancy is primarily attributed to slippage between the CFS and concrete, resulting from the smooth surface texture of the CFS, which limits effective bond formation. To address these challenges, shear connectors are proposed to enhance the CFS-concrete bond, aiming to boost load-carrying capacity. Therefore, this study aims to investigate hybrid beams reinforced with the CFS, focusing on ultimate load, deflection, ductility, and failure patterns. Six beams, varying in the CFS shape and shear connector type, underwent 3-point flexural testing. The results showed an impressive increase in ultimate load, of approximately 87.33%, and notable deflection reductions, ranging from 15.4% to 81.9%, compared to control beams. However, beam ductility decreased significantly, with the largest reduction observed at 78.83%, while flexural failure remained the predominant mode across all specimens.